2017
DOI: 10.1177/1066896917700725
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Triton Tumor (Malignant Peripheral Nerve Sheath Tumor With Rhabdomyoblastic Differentiation) Occurring in a Vascularized Free Flap Reconstruction Graft

Abstract: Malignant peripheral nerve sheath tumor (MPNST) is a rare form of sarcoma arising from Schwann cells or pluripotent cells of the neural crest. Malignant triton tumor (MTT) is a subtype of MPNST with a component of malignant rhabdomyoblasts in addition to malignant Schwann cells. MPNST and MTT are both aggressive malignancies that most commonly arise from large deep neurofibromas in patients with neurofibromatosis type 1 (NF-1). However, sporadic non-NF-1 cases of MTT have also been reported in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Malignant peripheral nerve sheath tumor (MPNST), a malignant neoplasm of Schwannian derivation, often shows heterologous rhabdomyosarcomatous divergent differentiation. When this happens, the tumor is often referred to as “malignant Triton tumor.” Although Schwann cells and melanocytes are both from neuroectodermal embryologic origin, melanomas appear to have a much lower propensity for heterologous rhabdomyosarcomatous differentiation than do MPNSTs. The reason for this difference is unclear.…”
Section: Discussionmentioning
confidence: 58%
“…Malignant peripheral nerve sheath tumor (MPNST), a malignant neoplasm of Schwannian derivation, often shows heterologous rhabdomyosarcomatous divergent differentiation. When this happens, the tumor is often referred to as “malignant Triton tumor.” Although Schwann cells and melanocytes are both from neuroectodermal embryologic origin, melanomas appear to have a much lower propensity for heterologous rhabdomyosarcomatous differentiation than do MPNSTs. The reason for this difference is unclear.…”
Section: Discussionmentioning
confidence: 58%
“…The latissimus dorsi myocutaneous ap is one of the largest skin aps that can be cut in the human body, and can be designed to cut various types of skin aps, muscle aps, myocutaneous aps, lobed myocutaneous aps and composite myocutaneous aps accoring to the characteristics of soft tissue defects 7 . In 1976, Baudet et al reported the successful case of free latissimus dorsi ap for the rst time, making the application of this ap in wound surface repair gradually widespread 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The histologic subtype of the soft tissue sarcomas is particularly notable, with half being rhabdomyosarcomas (sarcomas with skeletal muscle differentiation) and the other 2, malignant peripheral nerve sheath tumors (sarcomas with Schwann cell differentiation), with secondary heterologous rhabdomyosarcomatous transformation, a well-described phenomenon that has been referred to as malignant Triton tumor. We previously reported in a case report 26 the development of Triton tumor in the soft tissues after a trauma to the right proximal tibia, and this case was included in our series as case 6. This predilection for the development of a sarcoma in the skeletal muscle and nerve is fascinating in this context.…”
Section: Discussionmentioning
confidence: 99%